Citation analysis of the theses/dissertations submitted to the members of the Asia Graduate School of Theology - Philippines Consortium - Bugaay, Anelia N. (1997)
Analyzing the literature of a field of study can examine its growth and identify its characteristics as well as the problem orientations of the researchers in a subject area.